2023
DOI: 10.1111/jre.13203
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of a new synthetic carbonate apatite bone substitute on periodontal regeneration in intrabony defects

Jean‐Claude Imber,
Larissa Carmela Imber,
Andrea Roccuzzo
et al.

Abstract: ObjectiveTo evaluate the potential of a novel synthetic carbonate apatite bone substitute (CO3Ap‐BS) on periodontal regeneration.BackgroundThe use of various synthetic bone substitutes as a monotherapy for periodontal regeneration mainly results in a reparative healing pattern. Since xenografts or allografts are not always accepted by patients for various reasons, a synthetic alternative would be desirable.MethodsAcute‐type 3‐wall intrabony defects were surgically created in 4 female beagle dogs. Defects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Previous studies in humans [ 32 , 33 ], including a human autopsy [ 33 ], showed the histological and clinical behavior of biphasic material was effective, showing lamellar bone surrounding the remaining HA particles, suggesting that it served as scaffolding, and preserving its osteoconductive capabilities until it degraded. This process resulted in a stable graft material after 5 to 6 months of healing and allowed the dental implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans [ 32 , 33 ], including a human autopsy [ 33 ], showed the histological and clinical behavior of biphasic material was effective, showing lamellar bone surrounding the remaining HA particles, suggesting that it served as scaffolding, and preserving its osteoconductive capabilities until it degraded. This process resulted in a stable graft material after 5 to 6 months of healing and allowed the dental implant placement.…”
Section: Discussionmentioning
confidence: 99%